Sistem Informasi Pendataan dan Pengelolaan Rumah Rusak di Kecamatan Tangse - Khairani; Hajriyanti, Rahmi; Zahara, Rita (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The information system for damaged house data in Tangse District is designed to facilitate the management of damaged house data efficiently and accurately. This system aims to replace the manual process still in use by implementing computer-based software, enabling the data entry and processing of damaged houses to be carried out more quickly and easily. The system includes several key features, namely data input for damaged houses, data search, and report generation. Users can input data regarding damaged houses, search for previously entered data, and generate reports for printing. The process begins with user login, followed by the selection of the main menu to choose the desired function. The system is implemented using software such as Microsoft Access and Visual Basic, with normalization concepts applied to ensure data is well-organized and consistent. Evaluation results show that this system enhances work efficiency and data accuracy in managing damaged house information, providing convenience for the head of the subdistrict and related officers in making more precise decisions.